(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
his paper investigates the possibility for improving the performance level within the Libyan banking sector. A survey methodology was used for this study, along with customers’ observations and one-to-one interviews with a couple of decision makers and executive managers within the Jamhouriya Bank, investigating the current status for adapting the principles of Business Process Re-engineering (BPR). Based on the data analysis, the findings show that BPR is widely accepted by majority of the participants, whereas, the working environment needs to be prepared for adapting the BPR concepts throughout the entire banking operations, specifically the electronic services such as ATM cards. The finding also indicates that, improvements in the performance levels of the banking operations leads to improving the customer services in terms of cost reduction and fast services delivery. On the other hand, the results also pointed out that the surveyed organizations do not pay that much attention to some Critical Success Factors that being considered as crucial to implement BPR successfully. So, as a first step for efficiently adapting BPR, the most important issue is to ensure the top management support and allocating all the necessary resources. Only then increased customer satisfaction along with the profitability can be guaranteed within the Libyan banking business area